Football spectator no-show behavior in Switzerland: Empirical evidence from season ticket holder behavior - Dominik Schreyer; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2021)
For football executives, understanding the determinants of spectator no-show behavior better is of utmost importance. Recent research efforts, however, have primarily focused on exploring the potential effects of determinants that the club management can hardly influence (e.g., potential scheduling effects, the visiting team's quality, and the weather). In contrast, our understanding of factors relating to both accommodation (e.g., the ticket price), socio-demographics (e.g., age), and also emerging no-show habits, in predicting no-show behavior is still limited. Here, departing from more traditional survey-approaches, we address this shortcoming by exploring disaggregated behavioral season ticket holder data provided by an established Swiss Super League club. Analyzing a rich data set containing roughly 2.09 million attendance decisions made by ticket holders in Switzerland between 2013 and 2016, we observe that both a season ticket holder's accommodation and his (or her) socio-demographic information can help predict subsequent no-show behavior. In particular, we notice an important role of a season ticket holders' age, his (or her) domicile, and emerging no-show habits, as well as the season ticket price. Although our results suggest that the management of clubs with a strong demand for tickets might be well-advised to begin experimenting with strategies to exploit emerging no-show habits among their season ticket holders, most executives, i.e., those operating at clubs that sell-out their stadium only occasionally, might want to prioritize efforts to increase the inherent ticket value (e.g., by reducing the ticket supply).
Keywords: D12; L83; R22; Z20; 330; attendance; decision-making; demand; football/soccer; no-shows; seasontickets; spectator sports; stadiums